Internet of things: the concept, inherent security challenges and recommended solutions - Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Anwar, Farhat; Mir, Roohie Naaz; Oussama, Allama; Jusoh, Ahmad Zamani (Springer, Singapore, 2019)
The exponential growth observed as well as predicted in the development and deployment of the Internet of Things (IoT) based applications in every walk of our life brings forth the mandatory requirement of the secure communication system which is seamless yet effective in the highly heterogeneous and resource-constrained network. The core philosophy of the proposed research work is that existing cryptographic modelling will be required to be scaled down for its complexities by investigating the actual communication problems in security protocols between sensor nodes, Internet host, data centres, cloud clusters, virtual machines, etc. The inclusion of more operational actions while modelling security protocols is highly prioritised in the proposed research work. In this paper, the prime emphasis is (i) to establish secure pipelining using novel public-key cryptography between the sensor network and Internet host, (ii) a robust authentication scheme considering both local and global IoT to offer better secure pervasiveness in its applications, and (iii) to apply optimisation towards key management techniques.